Reviewing the regulation of dispute settlement mechanism for marine spatial utilization - Yulianti Rina; Pawestri Aprilina; Novitasari Risma Seli; Rachman Erio Agustia (BIO Web of Conferences)
The provisions of the marine spatial order are quite good in regulating control, especially the obligation for everyone to have a permit in the form of approval or confirmation of the suitability of marine space utilization activities issued by the Ministry of Maritime Affairs and Fisheries (KKP). Unfortunately, on the other hand, KKP only provides a mechanism for resolving disputes over marine spatial utilization in the administrative and Administrative Court (PTUN) for holders of KTUN in the form of Approval or Confirmation of KPRL. The characteristics of marine utilization activities can be categorized as follows: a) RZWP3K compliant and licensed activities, b) Activities not in accordance with RZWP3K and licensed, c) Activities in accordance with RZWP3K and not licensed. This character shows that the utilization of marine space is not only carried out by activities that have a permit or KPRL but also those that do not have a permit. Objections in this administrative effort only apply if what is disputed is KPRL as a KTUN product, it will be difficult if legality is not owned in the activities in these sea waters. For example, some conflicts over the utilization of marine space in the waters of the Sumenep Regency are slow to be resolved due to differences in perceptions of authority between the institutions or institutions that handle them. Dispute resolution mechanisms provided by the state in cases of marine space utilization need to be reviewed, especially strategies are needed related to the settlement model tailored to the character of the case.